Sealing material for underground space energy storage and preparation method thereof

By using high-crystalline sealing materials and using in-situ polymer monomers and other components to form a dense polymer network structure, the problem of insufficient sealing and deformation resistance of the closed materials for waste space gas storage in coal mines is solved, and efficient underground space gas storage effect is achieved.

CN119752315AActive Publication Date: 2025-04-04CCTEG COAL MINING RES INST +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411867638.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the prior art, the sealing materials for waste space gas storage in coal mines have insufficient sealing properties and insufficient deformation resistance, resulting in poor gas storage effect, which seriously affects the realization of underground space energy storage.

Method used

A high crystallinity sealing material is adopted, which consists of in-situ polymeric monomer, initiator, crystal nucleating agent, crystallization accelerator, dispersing agent, emulsifier and gelling material. It is prepared by spraying operation to form a dense polymer network structure to improve hermeticity and deformation resistance.

Benefits of technology

It achieves high sealing properties and excellent mechanical properties, significantly improves the effect of gas storage in underground space, and solves the problem of insufficient sealing properties and deformation resistance of sealed materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752315A_ABST
    Figure CN119752315A_ABST
Patent Text Reader

Abstract

The invention provides a sealing material for underground space energy storage and a preparation method thereof. The sealing material comprises the following components in parts by mass: 30-40 parts of an in-situ polymerization monomer, 1-2 parts of an initiator, 1-2 parts of a crystallization nucleating agent, 1-3 parts of a crystallization accelerant, 1-2 parts of a dispersant, 1-2 parts of an emulsifier and 90-100 parts of a cementing material. The sealing material provided by the invention is a high-crystallinity sealing material and has an outstanding sealing effect. The invention further provides a preparation method of the sealing material, and the preparation method has the characteristics of simple process, low cost and easiness in popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of green, low-carbon and new energy technologies such as underground space energy storage and gas storage, and in particular to a sealed material for underground space energy storage and a preparation method thereof. Background Art

[0002] Deep underground energy storage is an important direction for the development of energy reserves in the future. It is the only way to solve the problems of traditional oil strategic reserves, natural gas peak-shaving security, continuous supply of renewable energy, and large-scale and efficient utilization of hydrogen energy in the future. At present, there are many abandoned coal mines, large spaces, and low utilization rates. The maximum utilization of closed coal mines has not been achieved, resulting in a huge waste of underground space resources. The sealing problem of the gas seepage pathways formed in abandoned mines has made the key to gas storage in abandoned coal mine spaces. In the abandoned space of continuous rheological large deformation coal mines, the sealing material is not sufficiently sealed and has insufficient anti-deformation strength, which has limited sealing effect on the stored gas, seriously affecting the gas storage effect of the underground space and is the main constraint on underground space energy storage.

[0003] Therefore, there is an urgent need to develop new high-crystallinity sealed materials with high airtightness and excellent mechanical properties for underground space energy storage and their preparation methods and promote their application. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application proposes a sealing material for underground space energy storage and a preparation method thereof, the preparation method has the characteristics of simple process, low cost and easy promotion and application; the sealing material provided by the present application is a high-crystallinity sealing material with outstanding sealing effect.

[0005] According to an embodiment of the first aspect of the present application, a sealed material for underground space energy storage is proposed, comprising the following components in parts by mass: 30-40 parts of in-situ polymerization monomer, 1-2 parts of initiator, 1-2 parts of crystallization nucleating agent, 1-3 parts of crystallization promoter, 1-2 parts of dispersant, 1-2 parts of emulsifier and 90-100 parts of gelling material.

[0006] In some embodiments, the in-situ polymerized monomers include 4,4'-diphenylenediamine, pentachloroaniline, 2-chloroaniline, and 3-fluoroaniline in a mass ratio of 2:1:4:1.

[0007] In some embodiments, the initiator includes ammonium pyrosulfate and ammonium pyrosulfite in a mass ratio of 4:1.

[0008] In some embodiments, the crystal nucleating agent includes nano nickel ferrite and nano silicon nitride powder in a mass ratio of 1:1.

[0009] In some embodiments, the crystallization accelerator includes cellulose triacetate and cellulose nitrate in a mass ratio of 3:1.

[0010] In some embodiments, the emulsifier includes triethanolamine dodecylbenzenesulfonate and sodium dodecyldimethylbenzenesulfonate in a mass ratio of 1:1.

[0011] In some embodiments, the dispersant is monomethyl sebacate.

[0012] In some embodiments, the cementitious material is a sulphoaluminate cementitious material.

[0013] According to an embodiment of the second aspect of the present application, a method for preparing an underground space energy storage sealing material is proposed, comprising the following steps:

[0014] The sulphoaluminate gelling material, the crystallization nucleating agent, the dispersant and the crystallization accelerator are mixed uniformly according to the stoichiometric amount to obtain a closed base material;

[0015] The in-situ polymerization monomer, the initiator and the emulsifier are mixed according to the stoichiometric amount to obtain an active mixed solution;

[0016] The sealed base material is mixed with water at a water-cement ratio of 0.6 to obtain slurry A; the slurry A and the active mixed solution are sprayed at a volume ratio of 1:1 to obtain the sealed material described in any of the above embodiments.

[0017] According to an embodiment of the third aspect of the present application, a closed underground energy storage space is proposed, and the surface of the underground closed space is sprayed with the closed material described in any of the above embodiments to obtain the underground energy storage space.

[0018] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0020] Figure 1 It is a flow chart of a method for preparing a sealed material according to one embodiment of the present application. DETAILED DESCRIPTION

[0021] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0022] The technical solution of the embodiment of the present application provides a sealed material for underground space energy storage and a preparation method thereof. The present application provides a high-crystallinity sealed material that can be used for underground space energy storage. The preparation method has the characteristics of simple process, low cost and easy promotion and application.

[0023] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0025] To achieve the above-mentioned purpose, according to an embodiment of the first aspect of the present application, a sealed material for underground space energy storage is proposed, comprising the following components in parts by weight: 30-40 parts of in-situ polymerization monomer, 1-2 parts of initiator, 1-2 parts of crystallization nucleating agent, 1-3 parts of crystallization promoter, 1-2 parts of dispersant, 1-2 parts of emulsifier and 90-100 parts of gelling material.

[0026] Among them, in this embodiment, the sealing material includes 30-40 parts of in-situ polymerized monomers, for example, the in-situ polymerized monomers are 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, etc., wherein the in-situ polymerized monomers include 4,4'-diphenylenediamine (CAS: 92-87-5), pentachloroaniline (CAS: 527-20-8), 2-chloroaniline (CAS: 95-51-2), and 3-fluoroaniline (CAS: 372-19-0) in a mass ratio of 2: 1: 4: 1. If the number of in-situ polymerized monomers is small, such as less than 30 parts, the molecular weight of the in-situ cross-linked product is low, and the strength and airtightness of the sealing material are insufficient. If the number of in-situ polymerized monomers is large, such as greater than 40 parts, there are a large number of unreacted residual monomers, which affect the strength of the sealing material.

[0027] In some embodiments, the initiator is 1 part or 2 parts, etc., and the initiator includes ammonium pyrosulfate (CAS: 10031-68-2) and ammonium pyrosulfite (CAS: 32736-64-4) in a mass ratio of 4:1. If the number of initiators is small, such as less than 1 part, the reaction is not sufficient, and there are a large number of unreacted residual monomers, which affects the strength of the sealing material. If the number of initiators is large, such as more than 2 parts, the molecular weight of the in-situ cross-linked product is low, and the strength and airtightness of the sealing material are insufficient.

[0028] In some embodiments, the crystal nucleating agent may be 1 part or 2 parts, etc., which includes nano nickel ferrite (CAS: 12168-54-6) and nano silicon nitride powder (CAS: 12033-89-5) in a mass ratio of 1:1. If the crystal nucleating agent is used in a small amount, such as less than 1 part, the crystal nucleation effect is not good, the crystal nucleation and growth are not good, and the airtightness of the sealed material is not strong. If the crystal nucleating agent is used in a large amount, such as more than 2 parts, the crystal nucleation density is high, the crystal size is small, and there are many crystal defects, which affects the airtightness of the sealed material.

[0029] In some embodiments, the crystallization promoter may be 1 part, 2 parts or 3 parts, etc., and the crystallization promoter includes triacetate cellulose (CAS: 9012-09-3) and nitrocellulose (CAS: 132980-16-6) in a mass ratio of 3: 1. If the number of crystallization promoters is small, such as less than 1 part, the crystal nucleation effect is not good, the crystal nucleation and growth are not good, and the strength and airtightness of the sealed material are not strong. If the number of crystallization promoters is large, such as more than 3 parts, the crystal nucleation and growth rates are low, and there are many crystal defects.

[0030] In some embodiments, the emulsifier may be 1 part or 2 parts, etc., wherein the emulsifier includes triethanolamine dodecylbenzenesulfonate (CAS: 27323-41-7) and sodium dodecyl dimethylbenzenesulfonate (CAS: 63428-97-7) in a mass ratio of 1:1. If the emulsifier is used in a small amount, such as less than 1 part, the emulsification effect is poor and phase separation is likely to occur. If the emulsifier is used in a large amount, such as more than 2 parts, the mechanical strength and durability of the sealing material are affected.

[0031] In some embodiments, the powder may be 1 part or 2 parts, etc., wherein the powder includes monomethyl sebacate. If the powder is in a smaller amount, such as less than 1 part, the dispersion effect is poor and agglomeration is likely to occur. If the powder is in a larger amount, such as more than 2 parts, the mechanical strength and durability of the sealing material are affected.

[0032] In some embodiments, the cementitious material is a sulphoaluminate cementitious material, which includes 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or 100 parts, etc. If the cementitious material has a small part, such as less than 90 parts, the compressive strength and durability of the sealing material are insufficient. If the cementitious material has a large part, such as more than 100 parts, the sealing property of the sealing material is affected.

[0033] When the sealed base material and active mixed solution in this embodiment are used on site, the sealed base material is mixed with water at a water-cement ratio of 0.6 to obtain slurry A; slurry A and active mixed solution are sprayed at a volume ratio of 1:1 to obtain the sealed material in any of the above embodiments.

[0034] By incorporating aniline active monomers such as 4,4'-diphenylenediamine, pentachloroaniline, 2-chloroaniline, and 3-fluoroaniline into the gelling material, the gelling material hydration heat is used as the driving heat for in-situ polymerization at room temperature to form a dense and highly crystalline aniline polymer network, wherein the highly crystalline aniline polymer network causes the sealed material to lose fluidity and maintain a fixed shape to play a sealing role. The aniline polymer network and the hydration product of the gelling material form an interconductive network structure, that is, the dense and highly crystalline polymer network formed by in-situ polymerization at room temperature also forms a three-dimensional network structure, which can improve the mechanical properties of the sealed material and enable the sealed material to resist more deformation of underground space.

[0035] Among them, in-situ polymerization at room temperature forms a dense aniline polymer network. Due to the presence of a large number of amino groups, the number of hydrogen bonds in the system increases, the intermolecular force increases, and the number of hydrogen bonds has an important influence on the strength and wear resistance of the material, which can form a physical cross-linking effect and improve the strength of the sealed material. In addition, in-situ polymerization at room temperature forms a dense aniline polymer network, which promotes the nucleation and growth of the crystal of the sealed material under the action of the crystallization promoter, increases the crystallinity, and the dense crystal structure leads to a very dense molecular network structure, which can effectively achieve the sealing effect, and at the same time fill the pores of the gelling material, which can improve the sealing performance of the material.

[0036] The in-situ polymerization at room temperature forms a high-crystallinity polymer network. The increase in the grain size of the material will increase the interface area between the grains, and the interface area that can absorb the impact energy will also increase, and the impact resistance of the sealed material will also be improved accordingly. In addition, the increase in crystallinity will also affect the fracture mode and crack propagation speed of the material, thereby improving the impact performance of the material, so that the sealed material can effectively resist the deformation and impact of the underground space.

[0037] According to the embodiment of the second aspect of the present application, a method for preparing an energy storage sealing material for underground space is proposed. Figure 1 , including the following steps:

[0038] S1: mixing sulphoaluminate gelling material, crystal nucleating agent, dispersant and crystallization accelerator according to chemical measurement to obtain a closed base material; S2: mixing in-situ polymerization monomer, initiator and emulsifier according to chemical measurement to obtain an active mixed solution;

[0039] S3: Mix the sealed base material with water at a water-cement ratio of 0.6 to obtain slurry A; spray the slurry A and the active mixed solution at a volume ratio of 1:1 to obtain the sealed material in any of the above embodiments.

[0040] Among them, step S1, weigh 90-100 parts of sulphoaluminate gelling material, 1-2 parts of crystallization nucleating agent, and 1-3 parts of crystallization accelerator according to mass parts, stir them in a dry powder mixer for 15 minutes to mix them evenly, and obtain a closed base material.

[0041] In step S2, 30-40 parts of in-situ polymerization monomer, 1-2 parts of initiator, and 1-2 parts of emulsifier are weighed according to mass fractions, and stirred for 20 minutes to mix evenly to obtain an active mixed solution.

[0042] Step S3, during on-site use, the sealed base material is mixed with water at a water-cement ratio of 0.6 to obtain A material slurry, and the A material slurry and the active mixed solution are sprayed on the surface of the closed space at a volume ratio of 1:1 under the action of a double-liquid spraying pump to obtain a high-crystallinity sealed material.

[0043] According to an embodiment of the third aspect of the present application, a closed underground energy storage space is proposed, and the surface of the underground closed space is sprayed using the closed material in any of the above embodiments to obtain the underground energy storage space.

[0044] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.

[0045] Example 1

[0046] The present embodiment provides a sealed material for underground space energy storage, and its preparation method and specific operating parameters are as follows: 100 parts of sulphoaluminate gelling material, 2 parts of crystallization nucleating agent, 1 part of dispersant, and 1 part of crystallization promoter are weighed according to mass parts, and stirred in a dry powder mixer for 15 minutes to mix evenly to obtain a sealed base material; wherein the crystallization nucleating agent includes nano nickel ferrite and nano silicon nitride powder in a mass ratio of 1:1; the crystallization promoter includes triacetate fiber and nitrocellulose in a mass ratio of 3:1.

[0047] 30 parts of in-situ polymerization monomer, 1 part of initiator, and 1 part of emulsifier were weighed according to the mass fractions, and stirred for 20 minutes to mix evenly to obtain an active mixed solution. The in-situ polymerization monomers include 4,4'-diphenylenediamine, pentachloroaniline, 2-chloroaniline and 3-fluoroaniline in a mass ratio of 2:1:4:1; the initiator includes ammonium pyrosulfate and ammonium pyrosulfite in a mass ratio of 4:1; and the emulsifier includes triethanolamine dodecylbenzenesulfonate and sodium dodecyldimethylbenzenesulfonate in a mass ratio of 1:1.

[0048] The sealed base material is mixed with water at a water-cement ratio of 0.6 to obtain A material slurry. The A material slurry and the active mixed solution are sprayed on the surface of the closed space at a volume ratio of 1:1 under the action of a double-liquid spraying pump to obtain the sealed material.

[0049] Example 2

[0050] This embodiment is different from Embodiment 1 in the following aspects: 93 parts by mass of sulphoaluminate gelling material, 1 part of crystallization nucleating agent, 2 parts of dispersant, and 2 parts of crystallization accelerator are weighed; 33 parts by mass of in-situ polymerization monomer, 2 parts of initiator, and 1 part of emulsifier are weighed; the mixture is stirred for 20 minutes to be evenly mixed to obtain an active mixed solution.

[0051] Example 3

[0052] This embodiment is different from Embodiment 1 in the following aspects: 95 parts of sulphoaluminate gelling material, 2 parts of crystallization nucleating agent, 1 part of dispersant, and 2 parts of crystallization accelerator are weighed by weight, 36 parts of in-situ polymerization monomer, 1 part of initiator, and 2 parts of emulsifier are weighed by weight, and the mixture is stirred for 20 minutes to be evenly mixed to obtain an active mixed solution.

[0053] Example 4

[0054] This embodiment is different from Embodiment 1 in the following aspects: 98 parts of sulphoaluminate gelling material, 1 part of crystallization nucleating agent, 2 parts of dispersant, and 1 part of crystallization accelerator are weighed by mass; 40 parts of in-situ polymerization monomer, 2 parts of initiator, and 2 parts of emulsifier are weighed by mass; the mixture is stirred for 20 minutes to be evenly mixed to obtain an active mixed solution.

[0055] Example 5

[0056] This embodiment is different from Embodiment 1 in the following aspects: 90 parts by mass of sulphoaluminate gelling material, 2 parts by mass of crystallization nucleating agent, 1 part by mass of dispersant and 1 part by mass of crystallization accelerator are weighed; 38 parts by mass of in-situ polymerization monomer, 2 parts by mass of initiator and 1 part by mass of emulsifier are weighed; the mixture is stirred for 20 minutes to mix evenly to obtain an active mixed solution.

[0057] Experimental example

[0058] The sealing materials in each embodiment were tested after use, and the results are shown in Table 1.

[0059] Table 1 Performance results of the sealing materials in the embodiment

[0060]

[0061] It can be seen from the results in Table 1 that the sealing material provided by the present application is a high-crystallinity sealing material with outstanding sealing effect and strength.

[0062] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0063] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A sealed material for underground space energy storage, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of in-situ polymerization monomer, 1-2 parts of initiator, 1-2 parts of crystal nucleating agent, 1-3 parts of crystallization accelerator, 1-2 parts of dispersant, 1-2 parts of emulsifier and 90-100 parts of gelling material.

2. The sealing material according to claim 1, characterized in that: The in-situ polymerization monomers include 4,4'-diphenylenediamine, pentachloroaniline, 2-chloroaniline and 3-fluoroaniline in a mass ratio of 2:1:4:

1.

3. The sealing material according to claim 1, characterized in that: The initiator comprises ammonium pyrosulfate and ammonium pyrosulfite in a mass ratio of 4:

1.

4. The sealing material according to claim 1, characterized in that: The crystal nucleating agent comprises nano nickel ferrite and nano silicon nitride powder in a mass ratio of 1:

1.

5. The sealing material according to claim 1, characterized in that: The crystallization accelerator comprises cellulose triacetate and cellulose nitrate in a mass ratio of 3:

1.

6. The sealing material according to claim 1, characterized in that: The emulsifier comprises triethanolamine dodecylbenzenesulfonate and sodium dodecyldimethylbenzenesulfonate in a mass ratio of 1:

1.

7. The sealing material according to claim 1, characterized in that: The dispersant is monomethyl sebacate.

8. The sealing material according to any one of claims 1 to 7, characterized in that: The gelling material is a sulphoaluminate gelling material.

9. A method for preparing a sealed material for underground space energy storage, characterized in that: The following steps are involved: The sulphoaluminate gelling material, the crystallization nucleating agent, the dispersant and the crystallization accelerator are mixed uniformly according to the stoichiometric amount to obtain a closed base material; The in-situ polymerization monomer, the initiator and the emulsifier are mixed according to the stoichiometric amount to obtain an active mixed solution; The sealed base material is mixed with water at a water-cement ratio of 0.6 to obtain a material A slurry; the material A slurry and the active mixed solution are sprayed at a volume ratio of 1:1 to obtain the sealed material according to any one of claims 1-8.

10. A closed underground energy storage space, characterized in that: The surface of the underground enclosed space is sprayed with the enclosed material described in any one of claims 1 to 8 to obtain an underground energy storage space.

Citation Information

Patent Citations

  • Light-weight thermal-insulation concrete material and preparation method thereof

    CN111205032A

  • In-situ synergistic modified reinforced cement-based composite material and application thereof

    CN114436597A

  • Flame-retardant air-leakage-proof static non-reaction environment-friendly sealing and reinforcing composite thin spraying material

    CN115557762A

  • Double-network polymer in-situ toughened cement-based material and preparation method thereof

    CN117125938A

  • Nano-modified composite grouting material based on molecular orientation induced crystallization as well as preparation method and application of nano-modified composite grouting material

    CN117819908A